Princess Labelmaker to the Rescue! : Origami Yoda Series #5 - Angleberger, Tom (New York : Amulet Books, 2014)
One month before the state standards test are to take place, the Origami Rebel Alliance has found powerful allies in unexpected places in their fight against the FunTime test preparation program, but Principal Rabbski has not yet declared her allegiance.
Keywords: Finger puppets -- Fiction; Origami -- Fiction; Eccentrics and eccentricities -- Fiction; Interpersonal relations -- Fiction; Middle schools -- Fiction; Schools -- Fiction